2022
DOI: 10.3389/fpls.2021.795091
|View full text |Cite
|
Sign up to set email alerts
|

A Bitter-Sweet Story: Unraveling the Genes Involved in Quinolizidine Alkaloid Synthesis in Lupinus albus

Abstract: Alkaloids are part of a structurally diverse group of over 21,000 cyclic nitrogen-containing secondary metabolites that are found in over 20% of plant species. Lupinus albus are naturally containing quinolizidine alkaloid (QA) legumes, with wild accessions containing up to 11% of QA in seeds. Notwithstanding their clear advantages as a natural protecting system, lupin-breeding programs have selected against QA content without proper understanding of quinolizidine alkaloid biosynthetic pathway. This review summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…In lupin breeding, several different loci are known to control QA levels in L. angustifolius, L. albus, L. luteus and L. mutabilis; however, the identity of the underlying genes remains unknown. 72 Candidate genes have been proposed for the iucundus [73][74][75] and pauper 76,77 loci, but further work is needed to pinpoint single genes and establish causality. Similarly, mutagenized populations in a high-QA background may yield several low-QA mutant phenotypes, and the causative mutations can be identied in forward genetics approaches.…”
Section: Potential For Pathway Elucidation and Future Directionsmentioning
confidence: 99%
“…In lupin breeding, several different loci are known to control QA levels in L. angustifolius, L. albus, L. luteus and L. mutabilis; however, the identity of the underlying genes remains unknown. 72 Candidate genes have been proposed for the iucundus [73][74][75] and pauper 76,77 loci, but further work is needed to pinpoint single genes and establish causality. Similarly, mutagenized populations in a high-QA background may yield several low-QA mutant phenotypes, and the causative mutations can be identied in forward genetics approaches.…”
Section: Potential For Pathway Elucidation and Future Directionsmentioning
confidence: 99%
“…The toxic secondary plant metabolite, quinolizidine alkaloid (QA) in lupin seed proteins, is known for displaying both teratogenic and anti-cholinergic effects [127] . Aguilar-Acosta, Serna-Saldivar [128] determined low levels of lupanine (30 mg /100 g protein isolate) when extracting protein from Lupin mutabilis using UAE (US probe, 24 kHz, 100 % amplitude (100 μm), 85 W/cm 2 for 15 min).…”
Section: Impact Of Us On the Nutritional Profile Allergenicity And De...mentioning
confidence: 99%
“…Therefore, these investigated ecotypes suit lupin protein sources cultivated in both soils. However, the results of L. mutabilis raw seed characterization revealed that LC and LP ecotypes have an appreciable alkaloid content that must be removed before further analysis since these compounds have anti-nutritional properties [56]. Alkaloids have been previously reported in L. mutabilis seeds from plants collected in Ecuador [30] or Peru [57,58].…”
Section: Discussionmentioning
confidence: 99%